The “Trade-Off” of Student Well-Being and Academic Achievement: A Perspective of Multidimensional Student Well-Being - Ling, Xiaojun; Chen, Junjun; Chow, Daniel H. K.; Xu, Wendan; Li, Yingxiu (Frontiers in Psychology, 2022)
Student well-being and its relationships with academic achievement in China have not been well-investigated. This study aimed at investigating student well-being and the trade-off of the well-being and academic achievement with a sample of 1,353 Chinese high-school students from four cities in China during the COVID-19 pandemic period. The six dimensions of well-being (academic, psychological, self, physical, social, and spiritual) were utilised to test the relationships with three subjects including Mathematics, English, and Chinese using a quantitative analysis. In this study, the relationships between six dimensions of well-being and three academic subject achievement were tested in one statistical model. Results showed that spiritual well-being was ranked the highest, followed by psychological, physical, self, social well-being. Students gave the lowest ranking to academic well-being. The two significant paths identified were between spiritual well-being and two subjects, namely, Chinese and Mathematics. It is interesting to note that the other five dimensions of well-being were significantly associated with any subjects and English was not significantly related to any dimensions of well-being in the current study. Our findings suggested that policymakers and other stakeholders should avoid an ‘all or nothing’ mindset on practice when considering well-being as a multidimensional construct.